2017
DOI: 10.21037/jgo.2017.01.06
|View full text |Cite
|
Sign up to set email alerts
|

Combined dabrafenib and trametinib treatment in a case of chemotherapy-refractory extrahepatic BRAF V600E mutant cholangiocarcinoma: dramatic clinical and radiological response with a confusing synchronic new liver lesion

Abstract: Since the prognosis of advanced cholangiocarcinoma (CCA) remains poor with traditional chemotherapy, attention has shifted to molecularly targeted agents. Results of available clinical studies reveal little or no benefit of using targeted agents in advanced CCA. Limitations of these trials could be the lack of comprehensive molecular and genetic characterization of CCA samples in order to identify potential drug targets. Here we report a case of a 59-year-old female with chemotherapy-refractor, metastatic extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 28 publications
(40 reference statements)
0
11
0
5
Order By: Relevance
“…Sporadic case reports and case series regarding BRAFV600E-mutant BTC patients receiving dabrafenib plus trametinib combination have reported remarkable results, with cases of complete response to BRAFi plus MEKi. 65,66 In particular, Kocsis and colleagues reported the case of a 59-year-old BRAF V600E-mutated eCCA patient reporting complete response after dabrafenib plus trametinib combination treatment. 65 Of note, the included patient-whose disease progressed after first-line chemotherapy with cisplatin plus gemcitabine doublet-was firstly treated with dabrafenib orally 150 mg twice daily with subsequent addition of trametinib 2 mg once a day.…”
Section: Braf Mutations In Biliary Tract Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Sporadic case reports and case series regarding BRAFV600E-mutant BTC patients receiving dabrafenib plus trametinib combination have reported remarkable results, with cases of complete response to BRAFi plus MEKi. 65,66 In particular, Kocsis and colleagues reported the case of a 59-year-old BRAF V600E-mutated eCCA patient reporting complete response after dabrafenib plus trametinib combination treatment. 65 Of note, the included patient-whose disease progressed after first-line chemotherapy with cisplatin plus gemcitabine doublet-was firstly treated with dabrafenib orally 150 mg twice daily with subsequent addition of trametinib 2 mg once a day.…”
Section: Braf Mutations In Biliary Tract Cancermentioning
confidence: 99%
“…65,66 In particular, Kocsis and colleagues reported the case of a 59-year-old BRAF V600E-mutated eCCA patient reporting complete response after dabrafenib plus trametinib combination treatment. 65 Of note, the included patient-whose disease progressed after first-line chemotherapy with cisplatin plus gemcitabine doublet-was firstly treated with dabrafenib orally 150 mg twice daily with subsequent addition of trametinib 2 mg once a day. Similarly, Lavingia reported 2 cases of BRAF V600E-mutated iCCA treated with dabrafenib plus trametinib, reporting one complete response and a partial response, confirming the promising activity of dual BRAF and MEK targeting in these patients.…”
Section: Braf Mutations In Biliary Tract Cancermentioning
confidence: 99%
“…In addition, several case series have published good tolerability and response to this combination [ 22 , 23 , 24 ] and another phase-2 trial, VE-BASKET, demonstrated single agent efficacy of the BRAF inhibitor, vemurafenib, in BRAF V600E mutant cancers. In this study, a total of 208 patients with 26 different types of cancers were enrolled, including nine CCA patients.…”
Section: Potential Clinical Applications Of Molecular Profilingmentioning
confidence: 99%
“…In a phase II basket trial, only one patient out of 12 with iCCA demonstrated a partial response over a year of treatment with vemurafenib [89]. The combination of trametinib and dabrafenib was reported in case studies of advanced BTC with a BRAF V600E mutation and the results showed regression of metastatic lesions [90,91]. In a basket trial of rare tumors, including BTC harbouring BRAF V600E mutations, treatment with dabrafenib and trametinib resulted in an ORR of 42% in 35 patients with BTC [92].…”
Section: Mek and Braf Inhibitorsmentioning
confidence: 99%